La cartografia degli aggregati strutturali a supporto della salvaguardia dei beni culturali in emergenza - Cara, Pierluigi; Mercuri, Cosmo (Archeomatica, 2018)
Because of a significant seismic event, buildings of cultural interest are one of the first artifacts to suffer serious damage. In particular, churches are among of the most vulnerable types. However, finding and locating these buildings is a problem difficult to solve. This leads to delays and inefficiencies that could otherwise be avoided. The work proposes a method for the univocal and coordinated identification of such assets by cartography used for damage evaluation and the post-seismic surveying. In particular, an example of its application is made evident in the case of certain activities for the protection of cultural properties after the earthquake that hit Ischia Island on 21 September 2017